Influence of erotic television films on the sexual behaviour of adolescents in Ibadan, Nigeria (2013)
Media critics, particularly parents, point to the implicit treatment of sex in the mass media. Since adolescents are believed to be heavy users of the mass media, exposure to erotic television films may provide a springboard for sexual experimentation, without fear of contracting HIV. Previous studies have shown that exposure to mass media could influence attitude and behavior. However, empirical data examining the relationships between exposure to erotic television films and adolescents’ sexual behavior are rare. This study investigated the influence of erotic television films on sexual behavior of adolescent students in Ibadan metropolis. The study employed ex-post facto and Focus Group Discussion (FGD) research methods. Systematic sampling method was used in selecting a total of 800 adolescents between the ages of 14 and 18 from secondary and tertiary institutions, who responded to the questionnaire while purposive sampling technique was used in selecting 64 discussants who participated in the FGD. The data collected were analysed using descriptive statistics and One-Way ANOVA. Exposure to erotic television films showed a significant relationship with adolescent students’ risky sexual behavior (p<0.05). Scheffe post-hoc analysis revealed that more risky sexual behavior tended to be associated with greater exposure to erotic television films. FGD result showed that majority of the discussants believed that exposure to erotic television films could influence adolescents’ sexual behavior. The study established the influence of erotic television films on adolescent students’ risky sexual behavior. Considering the prevalence of HIV/AIDS among the adolescent group, broadcast regulatory agencies need to apply more stringent ethical measures in controlling the erotic content of films broadcast on television. Government and Non-Governmental Organisations should focus on intervention programmes aimed at reducing adolescent unsafe sexual activity.